Proton magnetic resonance spectroscopy in focal cortical dysplasia at 3 T. (November 2015) - Tschampa, Henriette J.; Urbach, Horst; Träber, Frank; Sprinkart, Alois M.; Greschus, Susanne; Malter, Michael P.; Surges, Rainer; Gieseke, Jürgen; Block, Wolfgang
Highlights: FCDs have a characteristic metabolic pattern in 1 H MRS at 3 T. FCD lesions show a significant increase of Cho and decrease of NAA. Frequency of seizures per day correlates with lesional Cr elevation. The metabolic pattern helps to differentiate FCDs from normal brain tissue. Abstract: Purpose: Focal cortical dysplasia (FCD) type II is a frequent cause of medically intractable epilepsy. On conventional MRI diagnosis may be difficult. The purpose of our study was to assess the metabolic characteristics of MRI-typical or neuropathologically confirmed FCD II lesions at 3 T. Methods: In a prospective study, 13 patients with drug-resistant epilepsy and MRI diagnosis of FCD II (seven neuropathologically confirmed) were investigated by single-volume proton magnetic resonance spectroscopy ( 1 H MRS). We performed an intra-individual comparison placing spectroscopic volumes of interest in the lesion and in the apparently normal contralateral hemisphere. Spectroscopic results were correlated with clinical data. Results: Matched pair analysis revealed a significant increase in absolute choline (Cho) concentration in the lesion volume (+32%, p  = 0.015) compared to the control volume. This increase was associated with a significant decrease in N-acetyl-aspartate (NAA) concentration (−13%; p  = 0.008). Mean myo-inositol (Ins) levels were distinctly (+36%) but not significantly ( p  = 0.051) elevated. Lesional creatine (Cr) concentration correlated significantly with the frequency of seizures (Spearman-Rho r  = 0.898; p  = 0.002), while concentrations of NAA, Cho and Ins did not correlate with clinical or imaging parameters. Conclusion: MR spectroscopy revealed a characteristic metabolic pattern in FCD II lesions that helps to distinguish normal from epileptogenic tissue.